Predicting the coronary atherosclerosis severity in cardiac patients - Yuri N. Fedulaev (Concilium Medicum, 2021)
Background. Coronary atherosclerosis is an ongoing pathological process, varying from asymptomatic forms to angina pectoris, myocardial infarction and even sudden cardiac death. Early identification of persons with an increased risk of the severe atherosclerosis will promote adequate diagnostic and therapeutic measures to prevent cardiovascular complications.